TEKNIK PERWUJUDAN PATUNG TRADISIONAL BALI PADA STUDIO KT. JAYA STONE BR. SENGGUAN, SINGAPADU, SUKAWATI, GIANYAR, BALI - I Kadek, Karang Arinatha; Suparta, I Made; Sumantra, I Made (Hastagina : Jurnal Kriya Seni, 2025)
The Internship/Work Practice Activity of the Independent Learning Independent Campus Program this time was carried out by the author at the KT. Jaya Stone Sculpture Studio located in Banjar Sengguan, Singapadu , Sukawati, Gianyar. The Studio Owner, in addition to as sculptor is also one of the skilled dance artists . The basic material used in making statue use processed waste rock that is easily found around the studio. The works the besides functioning profane there are also natures sacred in accordance with existing orders. Manufacturing process work at the beginning with demonstrate various dance moves for get quality character in accordance with desired figure. This internship program, the author wants to learn about the form and character of the work Paksi Dari, Monkey, Godogan (Frog), Sidakarya and dog using a rock. In the Independent Learning activity This Independent Campus writerFor tracing use method Exploration For get various character and nature Materials, Design For as well as know various existing dimensions in art statue Forget characteristics that exist in each figure like decoration, vehicle and manifestation Formore know every figure as well as movement, proportions and clothing used. Each method used Formake it easier do related searches with statue character Paksi Dedari who has graceful movements and character, Monkey who has facial expressions as if mocking his friends, Godogan (Frog), the mask character Sidakarya, Begawan, and motion naturalist dog.